2000
DOI: 10.1046/j.1432-1327.2000.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of Na+‐Ca2+ exchanger expression in guinea‐pig heart

Abstract: . (1996) J. Clin. Invest. 98, 1650±1658]. Although NCX expression was found to be significantly lower in the atria compared to the septum, no significant differences were found between atrial and ventricular tissue. NCX has been located in the general sarcolemma and t-tubules of ventricular muscle and as t-tubules are sparse in atrial tissue compared to ventricular tissue, it is surprising that NCX expression was found to be similar in both atria and ventricles [Wang et al. (1996)]. To reinvestigate this, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The bands of interest (arrows) are seen at 160, 120 and 70 kDa. Similar NCX bands in cardiac tissue have been described in several previous studies [9,10]. McDonald et al [10] identified these three bands as containing amino acid residues 371-525 of NCX and quantified regional NCX expression by summing immunosignals from each band for a given region.…”
Section: Quantification Of Ion Channel Subunit Protein By Western Blotmentioning
confidence: 57%
“…The bands of interest (arrows) are seen at 160, 120 and 70 kDa. Similar NCX bands in cardiac tissue have been described in several previous studies [9,10]. McDonald et al [10] identified these three bands as containing amino acid residues 371-525 of NCX and quantified regional NCX expression by summing immunosignals from each band for a given region.…”
Section: Quantification Of Ion Channel Subunit Protein By Western Blotmentioning
confidence: 57%
“…In all samples, an immunoreactive band at 120 kDa was evident, representing the mature NCX protein. Commonly, a weaker band was also observed at ≈ 70 kDa; this secondary band has been shown to be a proteolytic subfragment of the full‐length NCX (McDonald et al . 2000).…”
Section: Methodsmentioning
confidence: 99%
“…In all samples, an immunoreactive band at 120 kDa was evident, representing the mature NCX protein. Commonly, a weaker band was also observed at ~70 kDa; this secondary band has been shown to be a proteolytic subfragment of the full-length NCX (McDonald et al 2000). Analysis of band density was performed on both the 70 and 120 kDa signals and the two signals were summed to give the final NCX signal.…”
Section: Immunoblot-based Protein Quantificationmentioning
confidence: 99%
“…Probing for NCX1 yielded clear bands at 120kDa and 70kDa, as described in other studies using the same primary antibody. Because both bands have been shown to represent functional forms of NCX1, we included both in our analyses (McDonald et al, 2000). We found that the expression of Ca 2+ cycling proteins varied considerably and that the FFR did not correlate with NCX1 or SERCA2 (Figures 3B,C).…”
Section: Association Of Ca 2+ Cycling Proteins With Ffrmentioning
confidence: 99%